2008
DOI: 10.1002/pd.1907
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic assessment of the extra‐abdominal fetal small bowel in gastroschisis: a retrospective longitudinal study in relation to prenatal complications

Abstract: Dilatation of the extra-abdominal fetal small bowel in the third trimester may allow identifying fetuses with increased risk of fetal distress requiring closer monitoring of fetal well-being or delivery in a short interval to prevent impending fetal death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
19

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 25 publications
0
15
0
19
Order By: Relevance
“…The ultrasound markers considered for our study were: intrauterine growth restriction (IUGR) defined as estimated fetal weight <10th percentile [18], extra-abdominal bowel dilatation (EABD) of more than 13 mm at the second and 25 mm at the third trimester [19,20,21], stomach dilatation (antero-posterior diameter measurement >2 SD [22]), stomach herniation, perturbed mesenteric circulation as diagnosed by abnormal mesenteric artery color and pulse Doppler, absence of extra-abdominal intestinal lumen, and echogenic dilated bowel loops (EDBL) defined as visible bowel lumen measuring more than 2 mm in diameter with an echogenic wall [23]. Intra-abdominal bowel diameter was measured and expressed as the ratio of observed over expected measurement for gestational age, according to reference data established in normal fetuses [21].…”
Section: Methodsmentioning
confidence: 99%
“…The ultrasound markers considered for our study were: intrauterine growth restriction (IUGR) defined as estimated fetal weight <10th percentile [18], extra-abdominal bowel dilatation (EABD) of more than 13 mm at the second and 25 mm at the third trimester [19,20,21], stomach dilatation (antero-posterior diameter measurement >2 SD [22]), stomach herniation, perturbed mesenteric circulation as diagnosed by abnormal mesenteric artery color and pulse Doppler, absence of extra-abdominal intestinal lumen, and echogenic dilated bowel loops (EDBL) defined as visible bowel lumen measuring more than 2 mm in diameter with an echogenic wall [23]. Intra-abdominal bowel diameter was measured and expressed as the ratio of observed over expected measurement for gestational age, according to reference data established in normal fetuses [21].…”
Section: Methodsmentioning
confidence: 99%
“…While ultrasound for EFW was performed weekly by the majority of providers (79%; 104/131), at least two other studies disagreed on its ability to accurately predict adverse outcomes [27, 28]. There is also debate in the literature regarding the value of measuring bowel wall diameter and its relationship to outcomes, which may further explain the wide range of practices seen in our survey [6, 13, 15, 16, 29, 30]. …”
Section: Discussionmentioning
confidence: 74%
“…It appears, however, that antenatal screening cannot reliably predict morbidity, and the fact that no consensus emerges from the different studies is due mainly to the small sample size, but also to the difficulty in correlating imaging findings with clinical outcome. Some studies found a significant association between intra-abdominal bowel dilation and bowel atresia [5,17,18] . Japaraj et al [6] found that the occurrence of polyhydramnios was significantly associated with a higher rate of severe bowel com plications such as atresia, perforation and necrosis.…”
Section: Resultsmentioning
confidence: 99%